Phosphates galore: handle with care - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
For the last three years in Senegal, a total of 70,000 tons of phosphate fertilisers have been made available to farmers each year. This has been part of a programme of adding phosphates to increase the fertility of 300,000 hectares of land. The...